A novel model of large vessel ischemic stroke in rabbits: microcatheter occlusion of the posterior cerebral artery. (12th April 2014) - English, Joey D; Hetts, Steven W; El-Ali, Alex; Kolli, Pallav; Do, Loi; Wilson, Mark W; Saeed, Maythem
Abstract : Background and purpose: The rabbit small clot embolic model for large vessel occlusion (LVO) is well established, yet has limitations. Blind introduction of autologous thrombus often fails to completely occlude a target vessel and, when successful, the precise timing of occlusion and revascularization is difficult to control. Studies of cellular biology and neuroimaging of acute reversible cerebral ischemia (ie, penumbral tissue) would benefit from a rabbit model in which LVO can be reliably induced, easily confirmed, and in which the time of occlusion and revascularization can be precisely controlled. Methods: Transfemoral 1.5 F microcatheterization of the posterior cerebral artery (PCA) was performed in anesthetized rabbits (n=7) using fluoroscopic guidance. LVO with the wedged microcatheter was maintained for 30–210 min followed by reperfusion. Diffusion-weighted and T2 fluid-attenuated inversion recovery (FLAIR) MRI was performed 3 h after catheter removal on a 3 T scanner. Post-mortem histopathologic analysis of brain tissue was performed using triphenyltetrazolium chloride (TTC). Results: Placing of the 1.5 F microcatheter tip in the PCA was successful in all seven animals. Infarct size on matched diffusion-weighted and TTC sections was strongly correlated (r 2 =0.86). Transient PCA occlusion of 30–60 min resulted in infarction of the ipsilateral hippocampus and thalamus, sparing the cortex, while more prolonged occlusion (180–210 min) resulted in cortical infarction as well. Conclusions: Image-guided microcatheter induction of PCA occlusion in rabbits can consistently produce time-dependent infarction of cortical and subcortical structures that is reliably detected by diffusion-weighted MRI, and thus may be a useful model for therapeutic studies in acute ischemic stroke.